Intracerebral human regulatory T cells: analysis of CD4+CD25+FOXP3+ T cells in brain lesions and cerebrospinal fluid of multiple sclerosis patients - Fritzsching, Benedikt; Haas, Jürgen; König, Fatima; Kunz, Pierre; Fritzsching, Eva; Pöschl, Johannes; Krammer, Peter H.; Brück, Wolfgang; Suri-Payer, Elisabeth; Wildemann, Brigitte (PLOS ONE, 2011)
Impaired suppressive capacity of CD4+CD25+FOXP3+ regulatory T cells (Treg) from peripheral blood of patients with multiple sclerosis (MS) has been reported by multiple laboratories. It is, however, currently unresolved whether Treg dysfunction in MS patients is limited to reduced control of peripheral T cell activation since most studies analyzed peripheral blood samples only. Here, we assessed early active MS lesions in brain biopsies obtained from 16 patients with MS by FOXP3 immunohistochemistry. In addition, we used six-color flow cytometry to determine numbers of Treg by analysis of FOXP3/CD127 expression in peripheral blood and cerebrospinal fluid (CSF) of 17 treatment-naïve MS patients as well as quantities of apoptosis sensitive CD45ROhiCD95hi cells in circulating and CSF Treg subsets. Absolute numbers of FOXP3+ and CD4+ cells were rather low in MS brain lesions and Treg were not detectable in 30% of MS biopsies despite the presence of CD4+ cell infiltrates. In contrast, Treg were detectable in all CSF samples and Treg with a CD45ROhiCD95hi phenotype previously shown to be highly apoptosis sensitive were found to be enriched in the CSF compared to peripheral blood of MS patients. We suggest a hypothetical model of intracerebral elimination of Treg by CD95L-mediated apoptosis within the MS lesion.
Gesehen am 04.05.2023
Im Titel ist "+" hochgestellt